Case Study of N‐iPr versus N‐Mes Substituted NHC Ligands in Nickel Chemistry: The Coordination and Cyclotrimerization of Alkynes at [Ni(NHC)2]. Issue 71 (16th November 2021) - Tendera, Lukas; Helm, Moritz; Krahfuss, Mirjam J.; Kuntze‐Fechner, Maximilian W.; Radius, Udo
Abstract: A case study on the effect of the employment of two different NHC ligands in complexes [Ni(NHC)2 ] (NHC= i Pr2 Im Me 1 Me, Mes2 Im 2 ) and their behavior towards alkynes is reported. The reaction of a mixture of [Ni2 ( i Pr2 Im Me )4 ( μ‐(η 2  :  η 2 ) ‐COD)] B / [Ni( i Pr2 Im Me )2 ( η 4 ‐ COD)] B' or [Ni(Mes2 Im)2 ] 2, respectively, with alkynes afforded complexes [Ni(NHC)2 (η 2 ‐alkyne)] (NHC= i Pr2 Im Me : alkyne=MeC≡CMe 3, H7 C3 C≡CC3 H7 4, PhC≡CPh 5, MeOOCC≡CCOOMe 6, Me3 SiC≡CSiMe3 7, PhC≡CMe 8, HC≡CC3 H7 9, HC≡CPh 10, HC≡C( p ‐Tol) 11, HC≡C(4‐ t Bu‐C6 H4 ) 12, HC≡CCOOMe 13 ; NHC=Mes2 Im: alkyne=MeC≡CMe 14, MeOOCC≡CCOOMe 15, PhC≡CMe 16, HC≡C(4‐ t Bu‐C6 H4 ) 17, HC≡CCOOMe 18 ). Unusual rearrangement products 11 a and 12 a were identified for the complexes of the terminal alkynes HC≡C( p ‐Tol) and HC≡C(4‐ t Bu‐C6 H4 ), 11 and 12, which were formed by addition of a C−H bond of one of the NHC N ‐ i Pr methyl groups to the C≡C triple bond of the coordinated alkyne. Complex 2 catalyzes the cyclotrimerization of 2‐butyne, 4‐octyne, diphenylacetylene, dimethyl acetylendicarboxylate, 1‐pentyne, phenylacetylene and methyl propiolate at ambient conditions, whereas 1 Me is not a good catalyst. The reaction of 2 with 2‐butyne was monitored in some detail, which led to a mechanistic proposal for the cyclotrimerization at [Ni(NHC)2 ]. DFT calculations reveal that the differences between 1 M e and 2 for alkyne cyclotrimerization lie in the energy profile of the initiation steps, which is very shallow for 2, and each step is associated with only a moderate energy change. The higher stability of 3 compared to 14 is attributed to a better electron transfer from the NHC to the metal to the alkyne ligand for the N ‐alkyl substituted NHC, to enhanced Ni‐alkyne backbonding due to a smaller CNHC −Ni−CNHC bite angle, and to less steric repulsion of the smaller NHC i Pr2 Im Me . Abstract : Large versus small : The impact of two different NHC ligands in complexes [Ni(NHC)2 ] and the behavior of the complexes towards alkynes is presented. It demonstrates how small differences in the stereo‐electronic features of closely related ligands can significantly alter the reactivity pattern. The reaction of (suitable precursors of) both complexes with alkynes gave η 2 ‐( C, C )‐alkyne complexes [Ni(NHC)2 ]( η 2 ‐alkyne)], although the number of complexes available for [Ni(Mes2 Im)2 ] is limited to small alkynes and good acceptor alkynes.